1989
DOI: 10.1210/jcem-69-5-946
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Estrogens in Postmenopausal Insulin-Treated Diabetic Women

Abstract: Diabetic women may have an increased risk of developing endometrial carcinoma. Ovarian and adrenal activity seem to be factors in the genesis of this cancer. We have measured serum sex hormone-binding globulin (SHBG), free and bound fractions of estrogens and androgens, and gonadotropins in 20 consecutive postmenopausal insulin-treated diabetic women and 16 normal postmenopausal women. The diabetics were nonketoacidotic, without nephropathy and without proliferative retinopathy. The groups were comparable rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 31 publications
1
29
4
Order By: Relevance
“…Endometrial, postmenopausal breast, renal and less certainly gall bladder cancer risks have also been associated with obesity (International Agency for Research on Cancer, 2002), so the association of these cancers with type II diabetes might be a consequence of confounding by obesity. Oestrogen levels affect endometrial cancer risk (Grady and Ernster, 1996), but data are inconsistent on whether postmenopausal women with diabetes have raised oestrogen levels (Nyholm et al, 1989;Andersson et al, 1994). Possible mechanisms suggested for liver cancer in diabetes have included alcohol consumption and hepatitis (Verlato et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial, postmenopausal breast, renal and less certainly gall bladder cancer risks have also been associated with obesity (International Agency for Research on Cancer, 2002), so the association of these cancers with type II diabetes might be a consequence of confounding by obesity. Oestrogen levels affect endometrial cancer risk (Grady and Ernster, 1996), but data are inconsistent on whether postmenopausal women with diabetes have raised oestrogen levels (Nyholm et al, 1989;Andersson et al, 1994). Possible mechanisms suggested for liver cancer in diabetes have included alcohol consumption and hepatitis (Verlato et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In male subjects, studies have consistently found elevated testosterone in individuals with type 1 diabetes compared with that in control subjects (6,7). Studies in female subjects have demonstrated less coherence, with similar or elevated testosterone in both children (7) and adults (4,8) with type 1 diabetes compared with that in control subjects. These inconsistent results in female subjects could again be due to small samples.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Research on testosterone in male subjects with type 1 diabetes has consistently found elevated levels compared with those in control subjects (6), whereas studies in female subjects (children and adults) have been inconsistent, demonstrating comparable to higher levels of testosterone (4,7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the association between diabetes and breast cancer was strongest in Europe, followed by America, while it was non-significant in Asia (24). The biochemical and molecular associations between type 2 diabetes mellitus and breast cancer are outlined in Table 1 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), while the structure, uses, outcomes, and adverse reactions of metformin are shown in Table 2 (4,5,38,42,43). Metformin increases the effectiveness of neoadjuvant chemotherapy in breast cancer patients (44).…”
Section: Metforminmentioning
confidence: 99%